2016
DOI: 10.1021/jacs.6b08295
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Accelerated Copper Catalysis of Friedel–Crafts Conjugate Addition/Enantioselective Protonation Reactions in Water

Abstract: DNA-induced rate acceleration has been identified as one of the key elements for the success of the DNA-based catalysis concept. Here we report on a novel DNA-based catalytic Friedel-Crafts conjugate addition/enantioselective protonation reaction in water, which represents the first example of a reaction that critically depends on the >700- to 990-fold rate acceleration caused by the presence of a DNA scaffold. The DNA-induced rate acceleration observed is the highest reported due to the environment presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…It should be noted that the thioanisole substrate also shows a binding interaction with HT21 (Figures H and ). A similar phenomenon between substrates and metal cofactor/dsDNA hybrid catalysts was also found by Roelfes et al . It was proposed that these interactions of substrate and cofactor with dsDNA increased the effective molarity of substrate and cofactor, which resulted in rate acceleration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the thioanisole substrate also shows a binding interaction with HT21 (Figures H and ). A similar phenomenon between substrates and metal cofactor/dsDNA hybrid catalysts was also found by Roelfes et al . It was proposed that these interactions of substrate and cofactor with dsDNA increased the effective molarity of substrate and cofactor, which resulted in rate acceleration.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Roelfes et al. reported that the rate of Cu II –bipyridine catalyzing the Friedel–Crafts addition/enantioselective protonation reaction could be increased by as much as 990‐fold due to the presence of double‐stranded (ds) DNA . Spectral experiments suggested that Cu II –bipyridine interacted with dsDNA through groove binding The groove of dsDNA acted as a pseudophase to concentrate substrates, which resulted in the activity enhancement of the copper cofactor …”
Section: Introductionmentioning
confidence: 98%
“…A very recent study by Roelfes and co-workers [182] showed that upon binding of Cu(II) complexes, such as Cu(II)(dmbipy)(NO3)2 complex, to a DNA scaffold, the Friedel-Crafts reaction was enhanced >700-to 990-fold. DNA-accelerating effect was also observed for other reactions such as carbene-transfer reactions catalyzed by cationic iron-porphyrin [183], which suggests that DNA scaffolds are alternative to protein scaffolds, with potential applications in design of functional metalloenzymes.…”
Section: In Dimeric Protein Scaffoldsmentioning
confidence: 99%
“…21 These two reactions share similiraties, but the chiral center is created in different elementary reaction steps. 22 The conjugate addition of 5-methoxy-1H-indole (2b) to 2-methyl-1-(thiazol-2-yl)prop-2-en-1-one (4) was used as benchmark FC/EP reaction (Fig. 1d).…”
Section: Main Textmentioning
confidence: 99%